Factors influencing calving difficulty and gestation length in dairy cows inseminated with beef sires - R.H. Ahmed; C. Schmidtmann; J. Mugambe; G. Thaller (Animal)
Producing calves with higher economic value by utilising semen from beef breeds in dairy herds (Beef-on-Dairy, BoD) has become more common in recent times. Such crossbreed calves promise better carcass conformation and higher consumer acceptance due to the better flavour, but the widespread adaptation of BoD requires careful consideration of the sire breed to maximise the benefits. In this regard, two major traits of interest are calving difficulty and gestation length due to associated costs. In this study, 3 966 BoD calves from crossing Holstein dams with beef sires of the breeds Angus (n = 811), Belgian Blue (n = 2841), Limousin (n = 169) and Wagyu (n = 145) from 122 farms were evaluated to determine differences in calving difficulty and gestation length using binary logit and linear regression models. Lowest calving difficulty was observed for Wagyu crossbreds while Limousin crossbreds had the highest calving difficulty incidences. Selected sires from Angus and Belgian Blue breeds were also compared using chi-square analysis for differences in calving difficulty. The risk of calving difficulty was 1.94 times higher for male calves. Heifers had a significantly higher risk for calving difficulty when compared with the multiparous cows in the study. Calves with higher birth weight and longer gestation length were more prone to calving problems. For gestation length, Angus crossbreds had the shortest gestation (280.2 d), while the longest gestation (287.6) was observed in Limousin crossbreds. To maximise the benefits of the BoD breeding strategy, selecting appropriate sire breeds and within-breed sire selection for economically important traits, such as birth weight, appropriate gestation length, and reduced calving difficulty, may provide a viable solution.